2003
DOI: 10.1128/aac.47.1.255-261.2003
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Assay for Measurement of Intracellular DXG Triphosphate Concentrations in Peripheral Blood Mononuclear Cells from Human Immunodeficiency Virus Type 1-Infected Patients

Abstract: DXG {[2R-cis]-2-amino-1,9-dihydro-9-[2-[hydroxymethyl]-1,3-dioxolan-4-yl]-6H-purin-6-one} and its prodrug DAPD ([2R-cis]-4-[2,6-diamino-9H-purin-9-yl]-1,3-dioxolane-2-methanol; amdoxovir) are novel 2,3-dideoxynucleosides (ddNs) displaying activity against human immunodeficiency virus type 1 (HIV-1). In this paper, we describe the development of an enzymatic assay for determining the intracellular active metabolite of DXG and DAPD, DXG triphosphate (DXGTP), in peripheral blood mononuclear cells (PBMCs) from HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, these findings are not unexpected and are consistent with data from other studies of the NRTIs by several research groups using different methodologies. Large interpatient variation in both intracellular phosphorylation and plasma exposure of NRTIs have been reported previously (4,17,24,28,31,33,34,38). In addition, wide variation also exists in the intracellular concentrations of endogenous nucleoside triphosphates (16,17,24,37).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, these findings are not unexpected and are consistent with data from other studies of the NRTIs by several research groups using different methodologies. Large interpatient variation in both intracellular phosphorylation and plasma exposure of NRTIs have been reported previously (4,17,24,28,31,33,34,38). In addition, wide variation also exists in the intracellular concentrations of endogenous nucleoside triphosphates (16,17,24,37).…”
Section: Discussionmentioning
confidence: 94%
“…The study design used a parallel comparison between the patients receiving peginterferon alfa-2a (40KD) plus RBV and patients receiving peginterferon alfa-2a (40KD) plus placebo. However, as it is known that the concentrations of intracellular NRTI phosphates are highly variable (4,17,24,28,31,33,34,38), baseline values prior to the study or placebo administration were also collected for each of the arms (to measure the differences in the two arms at baseline). Furthermore, this design was chosen as previous data have suggested that intracellular NRTI phosphate levels change longitudinally with time (17).…”
Section: Methodsmentioning
confidence: 99%
“…The decay half-life of the active metabolite DXG-TP was ϳ16 h in activated primary human lymphocytes and ϳ9 h (or 27 h if including a 48-h time point) in humans, suggesting that twice a day (b.i.d.) dosing should provide adequate therapeutic coverage (26,30). Cellular toxicity studies suggested that AMDX and DXG did not affect the levels of mitochondrial DNA in human hepatoma cells (HepG2 cells) treated for 14 days at 10 M, and there was no increase in lactic acid production in these cells (9).…”
mentioning
confidence: 99%
“…Drug resistant HIV mutants susceptible to DXG in vitro include viruses containing M184V/I and thymidine analog mutations (TAMs: M41L, D67N, K70R, L210W, T215Y/F, K219Q/E), and the 69SS double insert [82]. The t 1/2 of DXG-TP was ~16 hr in activated primary human lymphocytes and ~9 hr (or 27 hr including a questionable 48 hr time point) in humans, suggesting that twice a day (bid) dosing should provide adequate therapeutic coverage [83]. AMDX and DXG did not affect the levels of mtDNA in human hepatoma cells (HepG2) treated for 14 days at 10 μM, and there was no increase in lactic acid production in these cells [84].…”
Section: Nrti In Developmentmentioning
confidence: 99%